Perlindungan Hukum bagi Aparatur Sipil Negara (ASN) dari Intervensi Politik dalam Pemilihan Kepala Daerah - Cahyadi, Cahyadi; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
ABSTRACT The neutrality of the State Civil Apparatus (ASN) is fundamental to bureaucratic professionalism and democratic regional elections (Pilkada). However, ASN members remain vulnerable to local political interventions such as mobilization of support, intimidation, and threats of demotion. Using a normative legal method with statutory, conceptual, and case approaches, this study analyzes the legal basis of neutrality, forms of intervention, legal protection mechanisms, and enforcement effectiveness in Pilkada. The results show that although regulations under Law Number 20 of 2023 on ASN and related rules are comprehensive, legal protection for ASN remains inadequate. Main obstacles stem from structural dependency on regional heads, bureaucratic patronage, institutional fragmentation, and weak follow-up on violations. Therefore, strengthening legal protection requires strict sanctions, whistleblower protection guarantees, merit system enforcement, inter-agency oversight coordination, and legal certainty in handling neutrality violations.